Wanted: suppliers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Wanted: suppliersA straightforward appeal to producers who can supply corn, maize, rice, sorghum, and millet for use in making animal and poultry feeds comes from C Loutangou of BP 2085, Mvoumvou, Pointe-Noire, Congo. Please contact him directly.